Subiektywne rozumienie bycia zdrowym wśród studentów pielęgniarstwa i ratownictwa medycznego – badanie wstępne = The subjective understanding of being healthy among students of nursing and medical rescue – a preliminary study - Wasil, Anna; Pietraszek, Agata; Charzyńska-Gula, Marianna; Nowicki, Grzegorz (Journal of Education, Health and Sport, 2016)
Wasil Anna, Pietraszek Agata, Charzyńska-Gula Marianna, Nowicki Grzegorz. Subiektywne rozumienie bycia zdrowym wśród studentów pielęgniarstwa i ratownictwa medycznego – badanie wstępne = The subjective understanding of being healthy among students of nursing and medical rescue – a preliminary study. Journal of Education, Health and Sport. 2016;6(4):493-502. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50708 http://ojs.ukw.edu.pl/index.php/johs/article/view/3499 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 28.04.2016. Subiektywne rozumienie bycia zdrowym wśród studentów pielęgniarstwa i ratownictwa medycznego – badanie wstępne The subjective understanding of being healthy among students of nursing and medical rescue – a preliminary study Anna Wasil1, Agata Pietraszek1, Marianna Charzyńska-Gula2, Grzegorz Nowicki1 1. Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu Streszczenie Wstęp: Najcenniejszą wartością dla człowieka jest zdrowie, które może przyjmować różne oblicze w zależności od wieku, płci, wykształcenia czy sytuacji społeczno-ekonomicznej. Sposób postrzegania pojęcia „zdrowie” wpływa w dużej mierze na zachowania zdrowotne, które kreują styl życia jednostki. Młodzież akademicka jest tą grupą społeczną, która w procesie socjalizacji podlega częstym próbom eksperymentowania, naśladowania, wybierania i w konsekwencji zmieniania otrzymanych w okresie dzieciństwa i młodości wzorców zachowań, bardzo istotnych ze względu na ryzyko pojawienia się kryzysu zdrowotnego lub też utrzymania dobrego potencjału zdrowia. Cel: Celem badań było poznanie opinii studentów pielęgniarstwa i ratownictwa medycznego dotyczącej znaczenia pojęcia „bycia zdrowym”, które w języku potocznym obrazuje kluczową dla badań subiektywną definicję zdrowia. Materiał i metody: W pracy wykorzystano metodę sondażu diagnostycznego z wykorzystanie dwóch narzędzi: autorskiego kwestionariusza ankiety oraz standaryzowanego narzędzia badawczego-Listy Kryteriów Zdrowia. Wyniki i wnioski: Badana młodzież akademicka uważa „bycie zdrowym” za bardzo istotną wartość w życiu każdego człowieka. Co więcej, zdecydowana większość badanych uważa się za osoby zdrowe a swój styl życia uważa za prozdrowotny. Określenie zdrowia przez studentów dotyczyło głównie jego wymiaru fizycznego. Być zdrowym to w przekonaniu badanych „mieć sprawne wszystkie części ciała”, „nie odczuwać żadnych dolegliwości fizycznych” oraz „czuć się dobrze”, szczególnie dla mężczyzn i studentów kierunku ratownictwo medyczne. W przypadku kobiet w subiektywnym postrzeganiu „bycia zdrowym” częściej istotne było „dożyć późnej starości”. Słowa kluczowe: umiejętność dbania o zdrowie; zdrowie kobiety; zdrowie mężczyzny; studenci zawodów medycznych. Abstract Introduction: Health is the most treasured value which can taken on different forms depending on age, gender, education or the socioeconomic situation of a person. The perception of the notion of health has a considerable impact on health behaviours, which shape people’s lives. University students constitute a social group which, in the process of socialisation, often experiments with, imitates and chooses behaviour patterns that are often different from the models developed during childhood and adolescence, which is very crucial due to the risk of health crisis and for maintaining a high health potential. Objective: The purpose of the study was to identify the opinions of students of nursing and medical rescue on the meaning of "being healthy", which in everyday language represents a subjective definition of health of substantial value for research. Material and methods: The study was carried out with the use of a diagnostic survey and two tools – a self-designed questionnaire and a standardised research tool called the List of Health Criteria. Results and conclusions: The surveyed university students claimed that "being healthy" is an extremely important value in every individual’s life. Furthermore, a considerable majority of the respondents considered themselves to be healthy and leading a healthy lifestyle. The students’ perceptions of health referred mainly to the physical dimension of the notion. According to the surveyed, being healthy meant "having all body parts working properly" "not experiencing any physical discomfort" and "feeling well", especially for male students of medical rescue. In the case of female students, the subjective perception of "being healthy" often involved "living up to a ripe old age" as a major factor. Key words: health literacy; women’s health; men’s health; students health occupations.